Feudal alliances in a hyper-capitalist world: Power and organization in EVE Online. Issue 2 (1st June 2020) - Milik, Oskar; Webber, Nick
EVE Online is a massively multiplayer online game that has gained notoriety for player organizations boasting thousands of active members. The complexity of these groups presents substantial challenges, and leaders have explored multiple approaches to organization and governance. They often employ structures and language drawn from historical social systems, family or nationality to create social order. Here we examine the use of feudalism in EVE ‐ as a structure of power, an indicator of legitimacy and a mechanism of waging war. We demonstrate that even as leaders incorporate feudal language into their organizations, their application of these concepts is influenced by capitalism and individualism. We argue that the final social and economic system is neither truly feudal nor capitalist, but instead an accommodation between the two, shaped by player knowledge, experience and in-game needs. We conclude that such systems support legitimate structures of power, which encourage player participation and produce more sustainable player organizations.